Solvent Screening in Enhanced Distillation Processes on the Total Annual Cost (TAC) Basis - Luot, Tien Thi; Nguyen, Dang Linh; Cao, Thi Mai Duyen; Nguyen, Huu Tung (Old Journal, 2020)
Traditionally the screening of solvents is done by ranking the solvents in the order of the selectivity at infinite dilution. Selectivity at infinite dilution is therefore an important parameter for consideration in the screening of the solvents for an enhanced distillation process including an azeotropic or an extractive distillation process. When solvents are ranked in order of selectivity, the solvent with the highest selectivity is always considered to be the most promising solvent for a given separation. This may indicate that, in economic terms, the use of the solvent with the highest selectivity will always give the lowest total annual cost (TAC) of the enhanced distillation process. How correct is this assertion or how does the order of solvents ranked on the basis of TAC of distillation process vary with the order based on the selectivity of the solvents being considered? This, then, is the focus of this paper. The selectivities of the solvents capable of enhancing the relative volatility of the chosen mixture Ethanol – Water are determined by using the NRTL method for predicting activity coefficients of mixture components. By using the same NRTL (Non-Random Two Liquids) – predicted VLE (Vapor-Liquid Equilibrium) data in both the complete costing and in the determination of the selectivity at infinite dilution, a valid comparison of solvent ranking in terms of the TAC and selectivity at infinite dilution is possible. The obtained results show that for all cases the order of solvents when ranked on the basis of TAC is not the same as when ranked on the basis of selectivity. This means that in general, the matching of selectivity with the TAC for the solvents used in the enhanced distillation process (EDP) of each of the five cases is not perfect.